Gender Equality Actions of Female Religious Figures in Madura (A Study on Locality Gender) - Jannah, Hasanatul; Yunda Fitriyah (HUMANISMA : Journal of Gender Studies, 2025)
This study examines the actions taken by female religious leaders in Madura as a manifestation of gender equality. The implementation of gender equality actions is accumulated from activities, roles, efforts, positions, power, representation, contributions, and even in gender relation bargaining to advocate for gender equality. The research employs a phenomenological approach, aiming to understand the experiences of female religious leaders in Madura as an embodiment of gender equality in their daily lives as the central issue within the primary structure of this study. The main subjects of this research are two female religious leaders. Data collection, processing, and analysis are conducted in an integrated manner through phenomenological steps. The findings of this study indicate that Nyai, as a representation of female religious figures in Madura, enacts gender equality by serving as religious leaders and worship guides, leaders and caretakers of Islamic boarding schools, controllers of the tengka tradition, motivators and counselors, domestic affairs managers, and facilitators of public space access.